Cadmium as an endocrine disruptor : correlation with anterior pituitary redox and circadian clock mechanisms and prevention by melatonin - Jiménez Ortega, Vanesa (2012)
Fil: Jiménez Ortega, Vanesa. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España